Biodiesel from vegetable oil as alternate fuel for C.I engine and feasibility study of thermal cracking: A critical review. (15th June 2016) - Ramkumar, S.; Kirubakaran, V.
Highlights: The C.V of biodiesel is less than diesel of about 10% on volume and 15% on mass basis. Most forms of biodiesel and its blends with diesel have higher viscosity than diesel. Biodiesel's cost and by-product reduce its feasibility as a substitute fuel. TGA & DCS of Pungamia Oil shows that Thermal cracking is an alternate to Biodiesel. Abstract: The awareness about using eco friendly fuels like biodiesel is increasing every day. The Increase in global warming and energy crises due to fossil fuel has accelerated the search of bio fuels. Biodiesel is a promising fuel; it is available in a wide range in every part of the world. Most of the studies reveal that the performance of biodiesel is better than that of diesel. Except NOx, the major emissions are high in the case of fossil fuels. This paper reviews the performance and emission characteristics of biodiesel in C.I engines. The paper also reviews the influence of engine modifications, various additives, and various proportions of blends of biodiesel with diesel. The physical and thermal characteristics of biodiesel have a great influence in the performance and emission, and they are tabulated in this paper. This paper also attempts feasibility of admitting vegetable oil in IC engine through Thermal Cracking. Preliminary investigation shows encouraging results and reported in this paper.